2017
DOI: 10.5812/ircmj.42712
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Noise Exposure and Hearing Impairment among Spinning Workers in Iran

Abstract: Background: Hearing impairment (HI), resulting from noise exposure, can be incapacitating and irreversible. Objectives: The present study aimed to determine the relationship between noise exposure and HI among workers and employees in a spinning industry. Methods: This cross sectional study was conducted on 489 workers in a spinning industry in Iran during 2015. The census method was applied for the purpose of sampling. The hearing threshold of each ear was determined during work shifts, using Madsen audiometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…In other words, the probability of hearing loss is higher at higher frequencies. 38,39 Thus, it can be concluded that students suffered from more temporary threshold shift after a 1-hour exposure to high-frequency noise, and therefore their loudness perception decreased and subsequently they reported lower noise annoyance. As previously mentioned, SLFN (55.48 AE 4.81) was somewhat higher than SHFN (54.17 AE 7.68).…”
Section: Annoyance and Loudness Perception And Personality Traitsmentioning
confidence: 99%
“…In other words, the probability of hearing loss is higher at higher frequencies. 38,39 Thus, it can be concluded that students suffered from more temporary threshold shift after a 1-hour exposure to high-frequency noise, and therefore their loudness perception decreased and subsequently they reported lower noise annoyance. As previously mentioned, SLFN (55.48 AE 4.81) was somewhat higher than SHFN (54.17 AE 7.68).…”
Section: Annoyance and Loudness Perception And Personality Traitsmentioning
confidence: 99%
“…This reinforces that hearing consequences also depend on period of noise exposure 16. 22 Also in a Canadian study by Feder et al, of the sample population 42% reported ETN for >10 year resulted in HL. 23 Also in a study by Pelegrin et al, involving construction workers, those who had ETN of 16.2 ± 11.4 years suffered with Hl significantly more than those exposed for 10.2 ± 7.0 years.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast in Khoshakhlagh et al, noted that blue collar workers were more likely to suffer Hl compared to white collar. 22…”
Section: Discussionmentioning
confidence: 99%
“…Chronic exposure results in metabolic changes in cochlear hair cells and capillary vasoconstriction. In recent decades, the high incidence of NIHL in developing nations is due to absence of preemployment audiometric assessments and regular hearing check-up [18].…”
Section: Discussionmentioning
confidence: 99%